EFFECT OF DIETARY PROTEIN INTAKE ON BONE DENSITY IN OLDER ADULTS IN THE HEALTH, AGING, AND BODY COMPOSITION STUDY. (11th November 2018) - Weaver, A; Tooze, J; Cauley, J; Bauer, D; Tylavsky, F; Kritchevsky, S; Houston, D
Abstract: Lower dietary protein intake may contribute to age-related decreases in bone mineral density (BMD) that lead to osteoporosis and fractures. We examined the association between dietary protein intake and BMD, as well as change in BMD, within 1, 141 community-dwelling older adult participants of the Health, Aging, and Body Composition Study (mean age, 73.6 years; 49.0% male, 38.9% black). BMD at baseline and Year 6 was acquired from computed tomography (CT) scans of the L3 vertebra, and dual-energy x-ray absorptiometry (DXA) scans of the whole body and hip. Protein intake was measured from a food frequency questionnaire in Year 2. Baseline BMD and the five-year change in BMD was compared across tertiles of protein intake as a percentage of total energy intake [Prot1 < 13.1% ≤ Prot2 < 15.7% ≤ Prot3] with analysis of covariance, adjusting for age, gender, race, smoking status, alcohol consumption, education, physical activity, BMI, energy intake, osteoporosis medications, calcium and vitamin D supplement use, estrogen therapy, and osteoporosis diagnosis. Baseline CT-derived trabecular, cortical, and integral L3 BMD and DXA-derived whole body, thoracic spine, and lumbar spine BMD was highest in participants with ≥15.7% protein intake, and lowest in participants whose protein intake was <13.1% (all p<0.01). However, 5-year change in BMD was not associated with baseline dietary protein intake. Similar trends were observed in gender-stratified models and when examining intake relative to protein source (animal vs. vegetable). In summary, higher dietary protein intake was associated with greater baseline spine and whole body BMD in community-dwelling older adults.